Combination with third‐generation bisphosphonate (YM529) and interferon‐alpha can inhibit the progression of established bone renal cell carcinoma. Issue 8 (14th July 2015) - Kurabayashi, Atsushi; Inoue, Keiji; Fukuhara, Hideo; Karashima, Takashi; Fukata, Satoshi; Kawada, Chiaki; Shuin, Taro; Furihata, Mutsuo
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate whether the third‐generation nitrogen‐containing bisphosphonate (YM529) can inhibit the progression of established bone renal cell carcinoma (RCC) and to elucidate its mechanism. Antiproliferative effect and apoptosis induction of RCC cells and mouse osteoclasts by YM529 and/or interferon‐alpha (IFN‐α) were evaluated in vitro using cell counting and in vivo using soft X‐ray, the TUNEL method and tartrate‐resistant acid phosphatase stain. For the in vivo study, male athymic BALB/cA Jc1‐nu nude mice bearing human RCC cell line RBM1‐IT4 cells were treated with YM529 and/or IFN‐α. The biological activity of osteoclasts was evaluated using the pit formation assay. The antiangiogenetic effect by YM529 and/or IFN‐α was analyzed using micro‐vessel density and in situ mRNA hybridization. Osteoclast number in bone tumors was decreased in YM529‐treated mouse. YM529 also inhibited osteoclast activity and proliferation in vitro, whereas basic fibroblast growth factor expressions and micro‐vessel density within tumors were inhibited by IFN‐α. Neither YM529 nor IFN‐α alone significantly inhibited the growth of established bone metastatic tumors. Combined treatment with YM529 and IFN‐α may be beneficial in patients with human RCC bone metastasis. Their effects are mediated by osteoclast recruitment inhibition and inactivation by YM529 and antiangiogenesis by IFN‐α.